A blizzard of polar bears : a novel of suspense - Henderson, Alice (Henderson, Alice. Alex Carter, 2021)
Fresh off her wolverine study in Montana, wildlife biologist Alex Carter lands a job studying a threatened population of polar bears in the Canadian Arctic. Embedded with a small team of Arctic researchers, she tracks the majestic bears by air, following them over vast, snowy terrain, spending days leaning precariously out of a helicopter with a tranquilizer gun, until she can get down on the ice to examine them up close. But as her study progresses, and she gathers data on the health of individual bears, things start to go awry. Her helicopter pilot quits unexpectedly, equipment goes missing, and a late-night intruder breaks into her lab and steals the samples she's collected. She realizes that someone doesn't want her to complete her study, but Alex is not easily deterred. Managing to find a replacement pilot, she returns to the icy expanses of Hudson Bay. But the helicopter catches fire in midflight, forcing the team to land on a vast sheet of white far from civilization. Surviving on the frozen landscape is difficult enough, but as armed assailants close in on snowmobiles, Alex must rely on her skills and tenacity to survive this onslaught and carry out her mission.